Incidental learning of a grammatical feature from reading by Japanese learners of English as a foreign language. (July 2020) - Aka, Natsuki
Abstract: This study investigated the effects of incidental learning of one specific grammatical feature through reading. A total of 157 Japanese high school learners of English as a foreign language (EFL) participated in this study. During the intervention, the experimental group ( n  = 74) read five passages consisting of a total of 40 sentences that include to-infinitives used as nouns, whereas the participants in the control group ( n  = 83) also read the same number of reading passages, but with only 10 sentences consisting of to-infinitives used as nouns. The participants took pre- and post-intervention grammar tests to measure the effectiveness of the treatment. The results showed that the experimental group incidentally noticed and learned about the use of to-infinitives as nouns through reading. The findings indicated that learners pay attention to language forms even though their focus is on reading comprehension. The study shows that frequent exposure to target grammar items repeatedly helps learners notice a grammatical rule, which, in turn, contributes positively to incidental grammar acquisition.